Women on the Federal Bench – A Progress Report - Cedarbaum, Miriam Goldman (Columbia Journal of Gender and Law, 2000)
I am delighted to join the celebration of the tenth anniversary of the Columbia Journal of Gender and Law of which I have been a satisfied subscriber since its first issue. Eight years ago, I gave a speech on the history of women on the federal bench at a luncheon forum of the New York County Lawyers Association. At that time, of the 801 federal district judges in the United States, only sixty-two were women. Of the 241 federal court of appeals judges, only twenty were women. At the dawn of a new millennium eight years later, I am happy to report that the percentage of Article III federal judges who are women has grown from less than ten percent to almost fifteen percent, a move in the right direction. Since 1993, eighty-eight distinguished women have been appointed to the federal bench. Moreover, Columbia’s own Justice Ruth Bader Ginsburg was appointed Associate Justice of the Supreme Court of the United States in 1993. That appointment increased the percentage of women on the bench of the highest court of the United States from eleven percent (one of nine) to twenty-two percent (two of nine).